2010
DOI: 10.7748/nm2010.05.17.2.30.c7727
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ perceptions of justice in performance appraisals

Abstract: Of all the tasks undertaken by human resource managers, performance appraisals (PAs) are one of the most unpopular among employees (Meyer 1991, Murphy and Cleveland 1995, Holbrook 2002, Jackman and Strober 2003). As PA guides and plans show (Fletcher 2004, CatalystOne 2010), PAs can be implemented in similar ways in organisations throughout Europe and developed countries elsewhere. But, if employees perceive PA processes as unfair, they may reject the usefulness and validity of the information they receive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
0
14
0
8
Order By: Relevance
“…5 When employees perceive their appraisal as unfair, they may dismiss the information received and be unmotivated to change their behavior. 5 When employees perceive their appraisal as unfair, they may dismiss the information received and be unmotivated to change their behavior.…”
Section: Wwwnursingmanagementcommentioning
confidence: 99%
See 1 more Smart Citation
“…5 When employees perceive their appraisal as unfair, they may dismiss the information received and be unmotivated to change their behavior. 5 When employees perceive their appraisal as unfair, they may dismiss the information received and be unmotivated to change their behavior.…”
Section: Wwwnursingmanagementcommentioning
confidence: 99%
“…6 Fairness is the most important factor in employees' response to the appraisal. 5 Studying the review process For this study, nurse leaders in a Magnet ® recognized hospital system examined their existing performance appraisal process after receiving feedback that it was too subjective. 5 Studying the review process For this study, nurse leaders in a Magnet ® recognized hospital system examined their existing performance appraisal process after receiving feedback that it was too subjective.…”
Section: Wwwnursingmanagementcommentioning
confidence: 99%
“…Furthermore, "... they cause conflict between supervisors and subordinates and lead to dysfunctional behaviours" (Dessler, 2003). Other researchers have suggested that employees have higher job motivation when they perceive their performance assessments as fair and trustworthy (Vasset, Marnburg & Furunes, 2010). Overall, then, performance assessment literature within the corporate world has made some progress in seeking to identify ways in which existing modes of interaction between human resource management and employees can be used in performance assessment.…”
Section: Review Of the Effect Of Performance Assessment On Employees'mentioning
confidence: 99%
“…The challenge of establishing and maintaining consistency of practice in a dynamic radiation therapy department highlights the importance of having defined practice standards and a reliable process for assessing performance. Well-defined standards can provide a clear statement of what is important in performance and be used to motivate staff and provide feedback on performance 35. Performance appraisal must also provide adequate support and training for development needs 3,6.…”
Section: Introductionmentioning
confidence: 99%
“…Well-defined standards can provide a clear statement of what is important in performance and be used to motivate staff and provide feedback on performance. [3][4][5] Performance appraisal must also provide adequate support and training for development needs. 3,6 A tool that encompasses these features will facilitate effective performance appraisal and promote staff satisfaction and professional growth.…”
Section: Introductionmentioning
confidence: 99%